2014
DOI: 10.1002/clen.201400231
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Thiol‐functionalized Mesoporous Silica – Their Role for Heavy Metal Removal Efficiency

Abstract: A simple approach based on the covalent grafting of 3-mercaptopropyltrimethoxysilane groups onto the framework of two types of mesoporous silica C16 (surface area: 1568.72 m 2 /g; pore size: 3.07 nm) using hexadecyltrimethyl ammoniumbromide and C9 (surface area: 779.83 m 2 /g; pore size: 4.51 nm) using nonyltrimethyl ammoniumbromide as templates has been reported. Various techniques were employed to confirm the thiol functionalization. A considerable decline in the surface area, pore volume, and interestingly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Aer the introduction of mercapto groups by MPTMS, the BET value returned to the original value, which may be due to the existence of large amount of organic mercapto groups graed into CoFe 2 O 4 @SiO 2 mesopores. 27 On one hand, it shows the successful graing of -SH; on the other hand, it indicates that the BET value was not the main factor affecting the adsorption performance of CoFe 2 O 4 @SiO 2 -SH.…”
Section: Resultsmentioning
confidence: 92%
“…Aer the introduction of mercapto groups by MPTMS, the BET value returned to the original value, which may be due to the existence of large amount of organic mercapto groups graed into CoFe 2 O 4 @SiO 2 mesopores. 27 On one hand, it shows the successful graing of -SH; on the other hand, it indicates that the BET value was not the main factor affecting the adsorption performance of CoFe 2 O 4 @SiO 2 -SH.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, the calculated value of R L is also in the required range of 0 < R L < 1 for SG-AEMH (0.13) and MS-PEI (0.07), signifying a favourable adsorption of Cr(VI). 49,[69][70][71] Adsorption kinetics…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…As an example, Lee et al [22] reported the adsorption of Pb(II) and Cu(II) metal ions on mesoporous silica modified with organic amine and thiol functional groups and results reveal that the thiol-functionalized mesoporous silica adsorbents exhibit enhanced adsorption affinity for Pb 2+ than the amino-mesoporous silica. Moreover, other studies reported an excellent Hg removal efficiency on thiolated mesoporous silica compared to the aminated ones [23,25].…”
Section: Introductionmentioning
confidence: 95%